2019
DOI: 10.1016/j.wroa.2019.100032
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved metal adsorption capacities and fractionation in filter materials for use in stormwater bioretention facilities

Abstract: The dissolved metal adsorption and association was determined for ten different filter materials recommended and/or implemented in bioretention facilities. Batch adsorption and batch kinetic experiments were performed at lab-scale using both single and multi-metal solutions. Metal strengths and association were determined by sequential extraction analysis. All materials adsorbed metals and 90% of adsorption occurred within 1 h. However, as metal solutions became more complex, adsorption behavior changed. Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Bioretention system, also known as rain garden, biofiltration or biofilter, is a typical low impact development (LID) facility to purify runoff through the combined action of plants, soil media and microorganisms [1,2]. It has been proved to be effective for the removal of most pollutants in runoff, such as heavy metals [3,4], suspended sediment [5][6][7], grease [8], pathogenic bacteria [9,10], etc. However, many previous studies indicated that bioretention systems have a low and unstable nitrogen removal rate [11,12], especially of NO 3 − .…”
Section: Introductionmentioning
confidence: 99%
“…Bioretention system, also known as rain garden, biofiltration or biofilter, is a typical low impact development (LID) facility to purify runoff through the combined action of plants, soil media and microorganisms [1,2]. It has been proved to be effective for the removal of most pollutants in runoff, such as heavy metals [3,4], suspended sediment [5][6][7], grease [8], pathogenic bacteria [9,10], etc. However, many previous studies indicated that bioretention systems have a low and unstable nitrogen removal rate [11,12], especially of NO 3 − .…”
Section: Introductionmentioning
confidence: 99%
“…When media with greater organic matter content was compacted, flow rates were significantly decreased. The adsorption of dissolved metals in stormwater by ten commonly used filter materials was tested by Søberg, Winston, Viklander, and Blecken (2019) by adopting a laboratory batch and kinetic adsorption methodology with both single‐ and multimetal solutions. Filter materials comprised mixtures in various combinations of the following materials: sand, biochar, compost, pumice stone, chalk, clay, and silt.…”
Section: Bioretentionmentioning
confidence: 99%
“…Bioretention system, also known as rain garden, biofiltration or biofilter, is a typical low impact development (LID) facility to purify runoff through the combined action of plants, soil media and microorganisms [1,2]. It has been proved to be effective for the removal of most pollutants in runoff, such as heavy metals [3,4], suspended sediment [5][6][7], grease [8], pathogenic bacteria [9,10], etc. However, many previous studies indicated that bioretention systems have a low and unstable nitrogen removal rate [11,12], especially of NO3 --N. Sometimes even nitrogen "leaching" occurred [13] in the systems.…”
Section: Introductionmentioning
confidence: 99%